Actions of water extract from Cordyceps militaris in hyperuricemic mice induced by potassium oxonate combined with hypoxanthine. (24th December 2016) - Yong, Tianqiao; Zhang, Minglong; Chen, Diling; Shuai, Ou; Chen, Shaodan; Su, Jiyan; Jiao, Chunwei; Feng, Delong; Xie, Yizhen
Abstract: Ethnopharmacological relevance: Cordyceps militaris was recorded in the classic traditional Chinese medicine book with the main functions of "protecting liver and enhancing kidney functions", influencing serum uric acid levels. Aim of study: The aim is to investigate the hypouricemic effects and possible mechanism of C. militaris in hyperuricemic mice. Materials and methods: A water extract (WECM) was prepared by decocting C. militaris directly at 80 °C in water bath, followed by lyophilization. WECM at 50, 100 and 200 mg/kg was orally administered to hyperuricemic mice induced by potassium oxonate and hypoxanthine combinedly and allopurinol (5 mg/kg) was served as a positive control. Results: WECM exhibited excellent hypouricemic activity, which could decrease the serum uric acid levels of the hyperuricemic mice (306 μmol/L) to 189, 184 and 162 μmol/L at different doses respectively ( P <0.01), approaching the levels of normal mice (184 μmol/L). The urate transporter 1 (URAT1) protein levels of kidney at different doses of WECM were 28.15, 17.43, 9.03 pg/mL respectively, much lower than that in the hyperuricemia group (93.45 pg/mL, P <0.01); and suggested WECM may interact with URAT1. Docking simulations using modeled structure of URAT1 suggested that LYS145, ARG325, ARG477 and ASP168 of URAT1 are key functional residues of URAT1. Four active compounds in C. militaris were identified and their interaction energies with target were estimated between −200 and −400 kcal/mol. Conclusions: These findings suggested that C. militaris produced significant hypouricemic actions and the hypouricemic effects of WECM may be attributed to the inhibitive effect of WECM on URAT1 protein levels. The results of blood urine nitrogen and serum creatinine levels and liver, kidney and spleen coefficients showed that WECM have no negative impacts on liver, renal and spleen functions. The screened four active compounds using molecular docking method deserve further investigation in other work. Graphical abstract: Water extract of Cordyceps militaris (WECM) produced significant hypouricemic actions and these may be attributed to the inhibitive effect of WECM on URAT1 protein levels. The results of serum BUN and creatinine and liver, kidney and spleen coefficients showed that WECM have no negative impacts on liver, renal and spleen functions. Through homology modelling and molecular docking, it suggested that LYS145, ARG325, ARG477 and ASP168 of URAT1 are key functional residues and four compounds were identified from Cordyceps militaris as active ingredients by virtual screening.